Harm avoidance and depression, anxiety, insomnia, and migraine in fifth-year medical students in Taiwan - Chen, Ching-Yen (Neuropsychiatr Dis Treat, 2018)
PURPOSE: During medical school training, increased stress, depression, and anxiety are common. Certain personality traits, particularly harm avoidance (HA), may increase the risk of psycho-pathological disorders, insomnia, and migraine among medical students. This study evaluated the role HA may play on levels of stress, depression, anxiety, and insomnia among Taiwanese medical students starting their fifth and final year of medical school. PATIENTS AND METHODS: A series of self-report questionnaires were used to measure the severity of anxiety, depression, and insomnia, as well as somatic symptoms, particularly migraine headache, among 143 Taiwanese fifth-year medical students (94 males and 49 females). Most had normal or mild levels of anxiety, depression, insomnia, and migraine. RESULTS: HA personality trait was significantly associated with depression (all P ≤ 0.001) after adjusting for other factors. HA was not significantly associated with anxiety, insomnia, or migraine headache days. CONCLUSION: HA personality trait was significantly associated with depression among fifth-year medical students in Taiwan.